Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Argan and pine stands comparably improve soil organic matter levels and microbiome structure and function under semi-arid Mediterranean conditions - María Patiño-García; José A. Siles; José M. De la Rosa; José A. González-Pérez; Manuel Rubio; Pedro Martínez-Gómez; Felipe Bastida (Plant and Soil, 2026)
Background and aims Reforestation is widely promoted to mitigate soil degradation and desertification in semi-arid Mediterranean regions under future climate-change scenarios. The argan tree ( Argania spinosa ), a drought-resistant species, has been proposed as a potential alternative to pine ( Pinus halepensis). Methods We assessed soil physicochemical properties, organic matter (SOM) characteristics (content, molecular composition and thermogravimetric fractions), priming effects, microbial activity, and metagenomics-based characterization of microbial communities under argan and pine stands, compared to adjacent bare soil. Results Both argan- and pine-influenced soils showed significantly higher SOM content (12.13% and 11.74%, respectively) than bare soil (4.51%), with comparable increases in organic carbon and nutrient availability. SOM characterization revealed that vegetation cover promoted higher SOM chemical diversity and a greater proportion of labile and intermediate SOM fractions, but differences between both types of trees were subtle. Both covers induced higher priming effects than bare soil, without compromising SOM accumulation. Argan and pine induced similar taxonomic shifts in the microbial community, with Solirubrobacter predominating under both tree species, whereas Rubrobacter dominated in bare soil. Functional profiles were largely conserved between argan- and pine-influenced soil compared to bare soil, with differences limited to slight enrichments in glycan and amino acid metabolism pathways. Genes for inorganic phosphorus solubilization predominated in bare soil, whereas organic phosphorus mineralization pathways were more prevalent in vegetated soil. Conclusion Overall, argan-influenced soil exhibited physicochemical and microbial properties comparable to those under pine, supporting argan as a potential alternative for reforestation and land restoration in Mediterranean ecosystems under increasing aridity.

Consistent topsoil carbon density and driving factors in urban greenspaces and natural ecosystems - Beatriz Jiménez-Prieto; Pablo García-Palacios; Carmen Lorenzo-Rodríguez; Elena Aguilar-Santana; Josu G. Alday; Camelia Algora; Cristian Carrillo-Guzmán; Cristina Armas; Felipe Bastida; Leonor Calvo; María D. Carmona-Yáñez; Axel Campos-Castro; et al. (Plant and Soil, 2026)
Background Urban greenspaces have the potential to mitigate urban carbon footprints by storing soil organic carbon (SOC). Different management and plant communities associated with different types of urban greenspaces may hold contrasting SOC, as well as different proportions of particulate (POC) and mineral-associated organic carbon (MAOC). In addition, management could outweigh the effects of climate or soil properties as drivers of urban SOC storage, in contrast with natural environments. Methods We analyzed SOC, POC and MAOC densities (kg m −2 ) in topsoil (0-10 cm) across 27 cities in the Iberian Peninsula with contrasting climatic and edaphic conditions. At each city, we compared four types of urban greenspaces (golf courses, roundabouts, urban farms, and parks) with a nearby natural ecosystem. Results Results revealed that, despite large differences in their typology, contrasting urban greenspaces stored comparable topsoil SOC and MAOC densities to natural ecosystems. Golf courses and urban farms also showed similar POC density to natural ecosystems, whereas parks and roundabouts had lower amounts of this carbon fraction. Consistent with global natural patterns, MAOC dominated over POC in the topsoil, and both carbon fractions showed an inverse correlation with mean annual temperature. While MAOC exhibited saturation at higher SOC levels, POC steadily increased. Conclusion Although urban greenspaces are usually neglected in global soil carbon assessments, our study shows that, compared to natural ecosystems (median: 2.42 kg m −2 ; interquartile range: 1.77), these areas store an equally important density of carbon in the topsoil (median: 2.26 kg m −2 ; interquartile range: 1.30), and this carbon exhibits similar fraction dominance, temperature influence, and saturation across large spatial gradients.

Soil multifunctionality and changes in the microbiome community following the transition from forest to agriculture in southern Spain - Ricardo Andrés Oviedo Celis; Maria Patiño; Felipe Bastida; Cristhian Hernández Gamboa; José Antonio Pascual; Margarita Ros (Geoderma Regional, 2026)

The multifunctionality of ruderal ecosystems is highly resistant to climate change - Rocío Rodríguez; Antonio Gallardo; Luis Villagarcia; Guiyao Zhou; Tadeo Sáez-Sandino; Samuel Castejón; Ana López; Jesús G. P. Rodríguez; Felipe Bastida; Manuel Delgado-Baquerizo (Plant and Soil, 2026)
Background and aim The global-scale abandonment of rural areas is resulting in a mosaic of disturbed ecosystems dominated by ruderal vegetation. Yet, the impacts of climate change on the functioning of ruderal ecosystems remain virtually unknown. Methods We conducted a 4-year field experiment to evaluate, for the first time, the long-term impacts of warming and rainfall reduction on the capacity of a ruderal Mediterranean ecosystem to maintain multiple ecosystem services. Results We found that, in general, ruderal ecosystems are highly resistant to climate change with minor effects of warming and rainfall reductions on plant biodiversity and multiple ecosystem services. In fact, we detected small but positive impacts of climate change on certain individual services, with warming enhancing primary production and soil carbon stocks, whereas the combined effects of warming and rainfall exclusion significantly reduced soil carbon stocks. Variation partitioning analysis further revealed that climate accounted for the largest share of variation in both primary production and soil carbon stocks. Conclusions Our results highlight the complexity of climate change interactions in explaining the capacity of ruderal ecosystems to support multiple ecosystem services, and further highlight the overall resistance of these already disturbed ecosystems to climate change.

Excessive phosphorus (P) fertilization reduces the soil priming effect in a Mediterranean soil - Xiaohan Dong; Alfonso Vera; Celia García-Díaz; Carlos García; Weidong Zhang; Felipe Bastida (Applied Soil Ecology, 2026)

Land Use Interacts With Climate to Influence Microbial Diversity‐To‐Biomass Ratios Across Europe via Soil Organic Carbon and Nitrogen - José A. Siles; Alfonso Vera; Maëva Labouyrie; Johan van den Hoogen; Thomas W. Crowther; Ferran Romero; Leho Tedersoo; Carlos García; Arwyn Jones; Panos Panagos; Marcel G. A. van der Heijden; Alberto Orgiazzi; et al. (Molecular Ecology, 2025)
Ecosystem functioning is potentially dependent on the relationships between soil microbial diversity and biomass. Yet, it remains unclear how land use and climate influence these relationships. Here, we (i) analysed relationships and ratios between richness and biomass of bacteria and fungi in ~500 soils across Europe, including three land‐use types (woodlands, grasslands and croplands) and climates (cold, temperate and arid) and (ii) identified the driving factors of changes in richness:biomass (R:B) ratios. Richness and biomass of soil bacteria and fungi followed a unimodal pattern, with a peak in mid‐levels of biomass. This pattern was more evident in bacteria and more clearly exerted by land use than by climate. Bacterial R:B ratios decreased with land use in the following order: croplands > woodlands > grasslands. Fungal R:B ratios decreased as follows: grasslands > croplands > woodlands. Climate was found to interact with land use. In this way, arid climate tended to increase bacterial R:B ratios in the different land uses; however, the agricultural practices associated with croplands seem to buffer this effect. In fungi, the interactive effect of land use and climate was less straightforward than for bacteria. According to our models, soil organic carbon (SOC) and total nitrogen (N) in bacteria and SOC in fungi were identified as the primary predictors of R:B ratios. Therefore, factors related to climate and land‐use change with impact on SOC and N contents are potential disruptors of soil microbial R:B ratios. This study clarifies the diversity:biomass relationships across different land uses and climates.

Green manure from cover crops enhances pesticide degradation and soil biological health - Marina Aliste; Caridad Ros; Isabel Garrido; Carmen María Martínez; Alfonso Vera; José Siles; Fulgencio Contreras; Pilar Flores; Pilar Hellín; José Fenoll; Felipe Bastida (Journal of Hazardous Materials, 2025)

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

Soil Characteristics Rather Than Microbial Inoculation Determines The Effects Of Alternative Phosphorus-Fertilizers On Ryegrass Yield And The Soil Microbial Community - Celia García-Díaz; José A. Siles; Felipe Bastida; José Luis Moreno (Journal of Soil Science and Plant Nutrition, 2025)
With global phosphate rock resources declining for conventional fertilizers, there is growing interest in exploring alternative, more sustainable materials to enhance soil fertility and crop yield production. Additionally, leveraging microorganisms to improve phosphorus (P) availability in soils is an appealing approach for sustainable agriculture. This study evaluates the effects of different P-rich materials, including struvite (STRU), meat and bone meal (MBM), and phosphate rock (PR), combined with a microbial consortium with P-solubilizing and plant growth-promoting capabilities, on P availability and plant growth in two soils with contrasting physicochemical properties. To achieve these goals, a pot experiment was conducted to assess P content in soil, ryegrass, and microbial biomass, along with microbial enzyme activity and community composition using microbial fatty acid analysis. The experiment involved two soils with contrasting characteristics, amended with conventional monoammonium phosphate (CHEM), STRU, MBM, and PR, with or without microbial inoculation. Soil characteristics and the type of P fertilizer significantly influenced P availability, ryegrass uptake, and plant yield. Microbial inoculation did not increase soil P or ryegrass yield. Fatty acid analysis showed microbial community changes with soil characteristics and fertilizer. Struvite performed similarly to CHEM, while MBM was less effective than struvite but better than PR as a P fertilizer. Our study found that soil characteristics and the type of phosphate fertilizer affected soil P dynamics in the soil–plant system. Recycled P-based fertilizers offer sustainable alternatives to synthetic ones, potentially alleviating agricultural challenges.

Phenological stages of wheat modulate effects of phosphorus fertilization in plant-soil microbial interactions - Celia García-Díaz; José A. Siles; José Luis Moreno; Carlos García; Antonio Ruiz-Navarro; Felipe Bastida (Plant and Soil, 2025)
Aims Future phosphorus (P) fertilizer availability faces challenges due to limited phosphate rock mines and strict quality regulations regarding Cd contents in phosphate rock. In this study, conventional fertilization was partially substituted with meat bone meal (MBM), sludge (S), and the organo-mineral combination of S plus MBM (SMBM), in a wheat agroecosystem. Methods We investigated the impact of fertilization treatments and crop phenological stages on P availability, crop yield, and soil microbial responses. Analysis included enzyme activities, microbial biomass, and the composition of bacterial and fungal communities using metabarcoding. Additionally, we estimated functional genes related to the P cycle through qPCR. Crop yield and nutrient content in plants and soil were also determined. Results Replacing traditional fertilization with MBM and SMBM maintained crop yield at levels equivalent to conventional fertilization. S and SMBM produced 70% and 40% (respectively) more bioavailable P compared to conventional treatment (Trad). Significant differences between treatments in soil microbial biomass were observed in the flag leaf stage. S increased in 20% total soil microbial biomass compared to Trad. Crop phenology had a stronger impact on bacterial and fungal communities than fertilization treatments. The use of S enhanced microbial biomass and activity. Yield in both MBM and SMBM plots exhibited no statistically significant differences compared to traditional fertilization. Conclusion Organo-mineral fertilization emerges as a sustainable strategy for maintaining crop production while improving soil functionality. Our findings emphasize the primary influence of crop phenology on shaping soil microbial communities and influencing microbial biomass and functionality.

A comparison among EL-FAME, PLFA, and quantitative PCR methods to detect changes in the abundance of soil bacteria and fungi - José A. Siles; Roberto Gómez-Pérez; Alfonso Vera; Carlos García; Felipe Bastida (Soil Biology and Biochemistry, 2024)

Long-term restoration with organic amendments is clearer evidenced by soil organic matter composition than by changes in microbial taxonomy and functionality - José A. Siles; José M. De la Rosa; José A. González-Pérez; Vanesa Fernández-Pérez; Celia García-Díaz; José L. Moreno; Carlos García; Felipe Bastida (Applied Soil Ecology, 2024)

Unearthing the soil‐borne microbiome of land plants - Raúl Ochoa‐Hueso; David J. Eldridge; Miguel Berdugo; Pankaj Trivedi; Blessing Sokoya; Concha Cano‐Díaz; Sebastian Abades; Fernando Alfaro; Adebola R. Bamigboye; Felipe Bastida; José L. Blanco‐Pastor; Asunción de los Rios; et al. (Global Change Biology, 2024)
Plant–soil biodiversity interactions are fundamental for the functioning of terrestrial ecosystems. Yet, the existence of a set of globally distributed topsoil microbial and small invertebrate organisms consistently associated with land plants (i.e., their consistent soil‐borne microbiome), together with the environmental preferences and functional capabilities of these organisms, remains unknown. We conducted a standardized field survey under 150 species of land plants, including 58 species of bryophytes and 92 of vascular plants, across 124 locations from all continents. We found that, despite the immense biodiversity of soil organisms, the land plants evaluated only shared a small fraction (less than 1%) of all microbial and invertebrate taxa that were present across contrasting climatic and soil conditions and vegetation types. These consistent taxa were dominated by generalist decomposers and phagotrophs and their presence was positively correlated with the abundance of functional genes linked to mineralization. Finally, we showed that crossing environmental thresholds in aridity (aridity index of 0.65, i.e., the transition from mesic to dry ecosystems), soil pH (5.5; i.e., the transition from acidic to strongly acidic soils), and carbon (less than 2%, the lower limit of fertile soils) can result in drastic disruptions in the associations between land plants and soil organisms, with potential implications for the delivery of soil ecosystem processes under ongoing global environmental change.

Tomato growth and physiology as well as soil physicochemical and biological properties affected by ozonated water in a saline agroecosystem - Marta Díaz-López; Lucas Galera; Felipe Bastida; Emilio Nicolás (Science of The Total Environment, 2024)

Abiotic and biotic drivers of struvite solubilization in contrasting soils - Antonio RUIZ-NAVARRO; Manuel DELGADO-BAQUERIZO; Concha CANO-DÍAZ; Carlos GARCÍA; Felipe BASTIDA (Pedosphere, 2023)

Editorial farewell to Heribert Insam - Judith Ascher-Jenull; Felipe Bastida; Shiping Deng; Denny Rigby; Andrey Zaitsev (Applied Soil Ecology, 2023)

The effects of boron-enriched water irrigation on soil microbial community are dependent on crop species - Alfonso Vera; Felipe Bastida; María Patiño-García; José L. Moreno (Applied Soil Ecology, 2023)

Soils in warmer and less developed countries have less micronutrients globally - Eduardo Moreno‐Jiménez; Fernando T. Maestre; Maren Flagmeier; Emilio Guirado; Miguel Berdugo; Felipe Bastida; Marina Dacal; Paloma Díaz‐Martínez; Raúl Ochoa‐Hueso; César Plaza; Matthias C. Rillig; Thomas W. Crowther; et al. (Global Change Biology, 2023)
Soil micronutrients are capital for the delivery of ecosystem functioning and food provision worldwide. Yet, despite their importance, the global biogeography and ecological drivers of soil micronutrients remain virtually unknown, limiting our capacity to anticipate abrupt unexpected changes in soil micronutrients in the face of climate change. Here, we analyzed >1300 topsoil samples to examine the global distribution of six metallic micronutrients (Cu, Fe, Mn, Zn, Co and Ni) across all continents, climates and vegetation types. We found that warmer arid and tropical ecosystems, present in the least developed countries, sustain the lowest contents of multiple soil micronutrients. We further provide evidence that temperature increases may potentially result in abrupt and simultaneous reductions in the content of multiple soil micronutrients when a temperature threshold of 12–14°C is crossed, which may be occurring on 3% of the planet over the next century. Altogether, our findings provide fundamental understanding of the global distribution of soil micronutrients, with direct implications for the maintenance of ecosystem functioning, rangeland management and food production in the warmest and poorest regions of the planet.

The global biogeography of soil priming effect intensity - Chengjie Ren; Fei Mo; Zhenghu Zhou; Felipe Bastida; Manuel Delgado‐Baquerizo; Jieying Wang; Xinyi Zhang; Yiqi Luo; Timothy J. Griffis; Xinhui Han; Gehong Wei; Jun Wang; et al. (Global Ecology and Biogeography, 2022)
Aim Fresh carbon (C) inputs to the soil can have important consequences for the decomposition rates of soil organic matter (priming effect), thereby impacting the delicate global C balance at the soil–atmosphere interface. Yet, the environmental factors that control soil priming effect intensity remain poorly understood at a global scale. Location Global. Time period 1980–2020. Major taxa studied Soil priming effect intensity. Methods We conducted a global dataset of CO 2 effluxes in 711 pairwise soils with 13 C or 14 C simple C sources inputs and without C inputs from incubation experiments in which isotope‐labelled C was used to quantify fresh C‐induced rather than exudate‐induced priming. Results Soil priming effect intensity is predominantly positive. Soil texture and C content were identified as the most important factors associated with priming effects, with sandy soils from tropical and mid‐latitudes supporting the highest soil priming effect intensity, and soils with greater C content and fine textures from high latitudes maintaining the lowest soil priming effects. The negative association between C content and soil priming effect intensity was also indirectly driven by changing mean annual temperature, net primary productivity, and fungi : bacteria ratio. Using this information, we generated a global map of soil priming effect intensity, and found that the priming was lower at high latitudes and higher at lower latitudes. Main conclusions Global patterns of soil priming effect intensity can be predicted using environmental data, with soil texture and C content playing a predominant role in explaining in priming effects. These effects were also indirectly driven by climate, vegetation and soil microbial properties. We present the first global atlas of soil priming effect intensity and advance our knowledge on the potential mechanisms underlying soil priming effect intensity, which are integral to improving the climate change and soil C dynamics components of Earth System models.

Priming effects in soils across Europe - José A. Siles; Marta Díaz‐López; Alfonso Vera; Nico Eisenhauer; Carlos A. Guerra; Linnea C. Smith; François Buscot; Thomas Reitz; Claudia Breitkreuz; Johan van den Hoogen; Thomas W. Crowther; Alberto Orgiazzi; et al. (Global Change Biology, 2022)
Land use is a key factor driving changes in soil carbon (C) cycle and contents worldwide. The priming effect (PE)—CO 2 emissions from changed soil organic matter decomposition in response to fresh C inputs—is one of the most unpredictable phenomena associated with C cycling and related nutrient mobilization. Yet, we know very little about the influence of land use on soil PE across contrasting environments. Here, we conducted a continental‐scale study to (i) determine the PE induced by 13 C‐glucose additions to 126 cropland and seminatural (forests and grasslands) soils from 22 European countries; (ii) compare PE magnitude in soils under various crop types (i.e., cereals, nonpermanent industrial crops, and orchards); and (iii) model the environmental factors influencing PE. On average, PEs were negative in seminatural (with values ranging between −60 and 26 µg C g −1 soil after 35 days of incubation; median = −11) and cropland (from −55 to 27 µC g −1 soil; median = −4.3) soils, meaning that microbial communities preferentially switched from soil organic C decomposition to glucose mineralization. PE was significantly less negative in croplands compared with seminatural ecosystems and not influenced by the crop type. PE was driven by soil basal respiration (reflecting microbial activity), microbial biomass C, and soil organic C, which were all higher in seminatural ecosystems compared with croplands. This cross European experimental and modeling study elucidated that PE intensity is dependent on land use and allowed to clarify the factors regulating this important C cycling process.

Microbial traits determine soil C emission in response to fresh carbon inputs in forests across biomes - Chengjie Ren; Jieying Wang; Felipe Bastida; Manuel Delgado‐Baquerizo; Yuanhe Yang; Jun Wang; Zekun Zhong; Zhenghu Zhou; Shuohong Zhang; Yaoxin Guo; Sha Zhou; Gehong Wei; et al. (Global Change Biology, 2022)
Soil priming is a microbial‐driven process, which determines key soil–climate feedbacks in response to fresh carbon inputs. Despite its importance, the microbial traits behind this process are largely undetermined. Knowledge of the role of these traits is integral to advance our understanding of how soil microbes regulate carbon (C) emissions in forests, which support the largest soil carbon stocks globally. Using metagenomic sequencing and 13 C‐glucose, we provide unprecedented evidence that microbial traits explain a unique portion of the variation in soil priming across forest biomes from tropical to cold temperature regions. We show that microbial functional profiles associated with the degradation of labile C, especially rapid simple sugar metabolism, drive soil priming in different forests. Genes involved in the degradation of lignin and aromatic compounds were negatively associated with priming effects in temperate forests, whereas the highest level of soil priming was associated with β‐glucosidase genes in tropical/subtropical forests. Moreover, we reconstructed, for the first time, 42 whole bacterial genomes associated with the soil priming effect and found that these organisms support important gene machinery involved in priming effect. Collectively, our work demonstrates the importance of microbial traits to explain soil priming across forest biomes and suggests that rapid carbon metabolism is responsible for priming effects in forests. This knowledge is important because it advances our understanding on the microbial mechanisms mediating soil–climate feedbacks at a continental scale.

Large‐scale drivers of relationships between soil microbial properties and organic carbon across Europe - Linnea C. Smith; Alberto Orgiazzi; Nico Eisenhauer; Simone Cesarz; Alfred Lochner; Arwyn Jones; Felipe Bastida; Guillaume Patoine; Thomas Reitz; François Buscot; Matthias C. Rillig; Anna Heintz‐Buschart; et al. (Global Ecology and Biogeography, 2021)
Aim Quantify direct and indirect relationships between soil microbial community properties (potential basal respiration, microbial biomass) and abiotic factors (soil, climate) in three major land‐cover types. Location Europe. Time period 2018. Major taxa studied Microbial community (fungi and bacteria). Methods We collected 881 soil samples from across Europe in the framework of the Land Use/Land Cover Area Frame Survey (LUCAS). We measured potential soil basal respiration at 20 ºC and microbial biomass (substrate‐induced respiration) using an O 2 ‐microcompensation apparatus. Soil and climate data were obtained from the same LUCAS survey and online databases. Structural equation models (SEMs) were used to quantify relationships between variables, and equations extracted from SEMs were used to create predictive maps. Fatty acid methyl esters were measured in a subset of samples to distinguish fungal from bacterial biomass. Results Soil microbial properties in croplands were more heavily affected by climate variables than those in forests. Potential soil basal respiration and microbial biomass were correlated in forests but decoupled in grasslands and croplands, where microbial biomass depended on soil carbon. Forests had a higher ratio of fungi to bacteria than grasslands or croplands. Main conclusions Soil microbial communities in grasslands and croplands are likely carbon‐limited in comparison with those in forests, and forests have a higher dominance of fungi indicating differences in microbial community composition. Notably, the often already‐degraded soils of croplands could be more vulnerable to climate change than more natural soils. The provided maps show potentially vulnerable areas that should be explicitly accounted for in future management plans to protect soil carbon and slow the increasing vulnerability of European soils to climate change.

Use of Slaughterhouse Sludge in the Bioremediation of an Oxyfluorfen-Polluted Soil - Paloma Ávila-Pozo; Juan Parrado; Pablo Caballero; Marta Díaz-López; Felipe Bastida; Manuel Tejada (International Journal of Environmental Research, 2021)
The use of organic matter is a highly accepted environmental practice among scientists for the bioremediation of polluted soils. In this manuscript we study under laboratory conditions the bioremediation capacity of a new biostimulant obtained from slaughterhouse sludge in a soil polluted by the oxyfluorfen at a rate of 4 l ha −1 (manufacturer’s rate recommended) over a 90-day period. We determined its effects on dehydrogenase, urease, β-glucosidase and phosphatase activities, the soil microbial community structure and the evolution of the herbicide in soil. Possibly due to the high content of low molecular weight proteins in the biostimulant, the enzymatic activities were stimulated mainly at the beginning of the experiment. Soil biological parameters were inhibited in oxyfluorfen-polluted soil. At the end of the experiment and compared with the control soil, dehydrogenase, urease, β-glucosidase, and phosphatase activities significantly decreased by 47.8%, 50.5%, 36.4%, and 45.5% in the oxyfluorfen-polluted soil. At 5 days into the experiment, the use of the biostimulant in oxyfluorfen-polluted soils decreased soil enzymatic activities and microbial community inhibition. At the end of the incubation period the oxyfluorfen concentration had decreased by 60% in the polluted soil and amended with biostimulants. These results suggested that the use of this biostimulant with higher amounts of low molecular weight proteins and peptides had a positive effect on the remediating oxyfluorfen-polluted soils. Therefore, this study provides the use of a new biostimulant obtained from slaughterhouse sludge by enzymatic hydrolysis processes used in the bioremediation of a soil polluted by the oxyfluorfen herbicide.

Microhabitat heterogeneity associated with Vanilla spp. and its influences on the microbial community of leaf litter and soil - Gabriela Montes de Oca-Vásquez; Frank Solano-Campos; Bernal Azofeifa-Bolaños; Amelia Paniagua-Vasquez; José Vega-Baudrit; Antonio Ruiz-Navarro; Rubén López-Mondéjar; Felipe Bastida (Soil Ecology Letters, 2020)

Climatic vulnerabilities and ecological preferences of soil invertebrates across biomes - Felipe Bastida; David J. Eldridge; Sebastián Abades; Fernando D. Alfaro; Antonio Gallardo; Laura García‐Velázquez; Carlos García; Stephen C. Hart; Cecilia A. Pérez; Fernanda Santos; Pankaj Trivedi; Mark A. Williams; et al. (Molecular Ecology, 2020)
Unlike plants and vertebrates, the ecological preferences, and potential vulnerabilities of soil invertebrates to environmental change, remain poorly understood in terrestrial ecosystems globally. We conducted a cross‐biome survey including 83 locations across six continents to advance our understanding of the ecological preferences and vulnerabilities of the diversity of dominant and functionally important soil invertebrate taxa, including nematodes, arachnids and rotifers. The diversity of invertebrates was analyzed through amplicon sequencing. Vegetation and climate drove the diversity and dominant taxa of soil invertebrates. Our results suggest that declines in forest cover and plant diversity, and reductions in plant production associated with increases in aridity, can result in reductions of the diversity of soil invertebrates in a drier and more managed world. We further developed global atlases of the diversity of these important soil invertebrates, which were cross‐validated using an independent database. Our study advances the current knowledge of the ecological preferences and vulnerabilities of the diversity and presence of functionally important soil invertebrates in soils from across the globe. This information is fundamental for improving and prioritizing conservation efforts of soil genetic resources and management policies.

Differential sensitivity of total and active soil microbial communities to drought and forest management - Felipe Bastida; Irene F. Torres; Manuela Andrés‐Abellán; Petr Baldrian; Rubén López‐Mondéjar; Tomáš Větrovský; Hans H. Richnow; Robert Starke; Sara Ondoño; Carlos García; Francisco R. López‐Serrano; Nico Jehmlich (Global Change Biology, 2017)
Climate change will affect semiarid ecosystems through severe droughts that increase the competition for resources in plant and microbial communities. In these habitats, adaptations to climate change may consist of thinning—that reduces competition for resources through a decrease in tree density and the promotion of plant survival. We deciphered the functional and phylogenetic responses of the microbial community to 60 years of drought induced by rainfall exclusion and how forest management affects its resistance to drought, in a semiarid forest ecosystem dominated by Pinus halepensis Mill. A multi OMIC approach was applied to reveal novel, community‐based strategies in the face of climate change. The diversity and the composition of the total and active soil microbiome were evaluated by 16S rRNA gene (bacteria) and ITS (fungal) sequencing, and by metaproteomics. The microbial biomass was analyzed by phospholipid fatty acids ( PLFA s), and the microbially mediated ecosystem multifunctionality was studied by the integration of soil enzyme activities related to the cycles of C, N, and P. The microbial biomass and ecosystem multifunctionality decreased in drought‐plots, as a consequence of the lower soil moisture and poorer plant development, but this decrease was more notable in unthinned plots. The structure and diversity of the total bacterial community was unaffected by drought at phylum and order level, but did so at genus level, and was influenced by seasonality. However, the total fungal community and the active microbial community were more sensitive to drought and were related to ecosystem multifunctionality. Thinning in plots without drought increased the active diversity while the total diversity was not affected. Thinning promoted the resistance of ecosystem multifunctionality to drought through changes in the active microbial community. The integration of total and active microbiome analyses avoids misinterpretations of the links between the soil microbial community and climate change.

The active microbial diversity drives ecosystem multifunctionality and is physiologically related to carbon availability in Mediterranean semi‐arid soils - Felipe Bastida; Irene F. Torres; José L. Moreno; Petr Baldrian; Sara Ondoño; Antonio Ruiz‐Navarro; Teresa Hernández; Hans H. Richnow; Robert Starke; Carlos García; Nico Jehmlich (Molecular Ecology, 2016)
Biogeochemical processes and ecosystemic functions are mostly driven by soil microbial communities. However, most methods focus on evaluating the total microbial community and fail to discriminate its active fraction which is linked to soil functionality. Precisely, the activity of the microbial community is strongly limited by the availability of organic carbon (C) in soils under arid and semi‐arid climate. Here, we provide a complementary genomic and metaproteomic approach to investigate the relationships between the diversity of the total community, the active diversity and ecosystem functionality across a dissolved organic carbon ( DOC ) gradient in southeast Spain. DOC correlated with the ecosystem multifunctionality index composed by soil respiration, enzyme activities (urease, alkaline phosphatase and β‐glucosidase) and microbial biomass (phospholipid fatty acids, PLFA ). This study highlights that the active diversity (determined by metaprotoemics) but not the diversity of the whole microbial community (evaluated by amplicon gene sequencing) is related to the availability of organic C and it is also connected to the ecosystem multifunctionality index. We reveal that DOC shapes the activities of bacterial and fungal populations in Mediterranean semi‐arid soils and determines the compartmentalization of functional niches. For instance, Rhizobales thrived at high‐ DOC sites probably fuelled by metabolism of one‐C compounds. Moreover, the analysis of proteins involved in the transport and metabolism of carbohydrates revealed that Ascomycota and Basidiomycota occupied different nutritional niches. The functional mechanisms for niche specialization were not constant across the DOC gradient.